2019
DOI: 10.1111/jog.14116
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term oncological outcomes of minimally invasive radical hysterectomy for early‐stage cervical cancer: A retrospective, single‐institutional study in the wake of the LACC trial

Abstract: Aim: The objective of this study was to investigate the long-term oncological outcomes of minimally invasive radical hysterectomy (MIRH) for the treatment of early-stage cervical cancer retrospectively in the wake of the laparoscopic approach to cervical cancer (LACC) trial. Methods: A total of 109 patients with stage IA1 with lymphovascular space involvement, IA2, and IB1 cervical cancers were included in this study. The surgical and oncological outcomes were retrospectively evaluated. All patients underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…Generally, the survival after LRH in patients with stage IA-IB1 cervical cancer is satisfying but varies across studies, with a 5-year PFS rate ranging from 80.2-96.3% (5,8,15). In the present study, we also report a high 4-year PFS of 92.0% in patients, which is not inferior to that in the open surgery group of the LACC trial.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Generally, the survival after LRH in patients with stage IA-IB1 cervical cancer is satisfying but varies across studies, with a 5-year PFS rate ranging from 80.2-96.3% (5,8,15). In the present study, we also report a high 4-year PFS of 92.0% in patients, which is not inferior to that in the open surgery group of the LACC trial.…”
Section: Discussionsupporting
confidence: 58%
“…Several studies have provided retrospective evidence supporting some improvements in LRH to prevent possible tumor cell spillage. The survival after LRH with the "no-look no-touch technique" for stage IB1 tumors was found to be equal to that after open surgery (15). A multicenter analysis of 389 patients showed that LRH with transvaginal closure of the vaginal cuff avoided the use of a manipulator and offered oncologic outcomes similar to those of the laparotomy arm in the LACC trail (25).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors noted the routine use of a uterine manipulator and intracorporeal colpotomy under CO 2 circulation as two of several possible reasons for the inferior oncologic outcomes associated with minimally invasive approaches. Protective maneuvers of cancer cell spillage are regarded as mandatory to ensure oncologic outcomes [ 13 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is not suitable for nulliparous patients with a narrow vagina. In the transvaginal approach usually used by Japanese surgeons, the vaginal cuff is closed by continuous suture after cutting the vaginal mucosa pulled with silk stitches 3,9 . The traditional method closing the vaginal cuff is as follows.…”
Section: Discussionmentioning
confidence: 99%